WRKY43 regulates polyunsaturated fatty acid content and seed germination under unfavourable growth conditions - Geilen, Katja; Hillmer, Stefan (Scientific reports, 2017)
Seed germination and postgerminative growth of Arabidopsis thaliana and various other plant species are arrested in response to unfavourable environmental conditions by signalling events involving the phytohormone abscisic acid (ABA). In this study, we showed that loss of the seed-specific WRKY DNA-BINDING PROTEIN 43 (WRKY43) conferred increased tolerance towards high salt, high osmolarity and low temperature during seed germination in Arabidopsis. The wrky43 loss of function lines displayed increased inhibition of seed germination in response to exogenous ABA; whereas lines overexpressing WRKY43 were more tolerant towards exogenous ABA. Biochemical analysis of fatty acid composition revealed that loss of WRKY43 increased polyunsaturated fatty acid content in seeds, particularly 18:2Δ9,12 and 18:3Δ9,12,15 in triacylglycerols and phospholipids, indicating an important physiological effect on fatty acid desaturation with ramifications for the tolerance of plants to cold and osmotic stress and possibly, for oilseed engineering. Molecular analyses showed that ABA-induced regulation of FUSCA3, ZAT10 and seed storage proteins were absent in the wrky43 mutant. In summary, WRKY43 encodes for a novel positive regulator of ABA-dependent gene regulation and as a potent modulator of fatty acid desaturation and seed filling, which results in increased tolerance to abiotic stress.